Understanding local peoples’ participation as “means” and “ends” in protected areas management: a qualitative study in the heart of Borneo - Makoto Inoue; Daisuke Terauchi; Koji Fujii; Kazuki Tsunoda; Noriko Okubo; Yukari Takamura; Herman Hidayat; Ndan Imang; Martinus Nanang; Peter Voo Su Kiong; Tapan Kumar Nath (Taylor and Francis Ltd., 2021)
Local people’s’participation is highly recommended in protected areas (PAs) management. This study aimed at understanding local people’s participation as “means” or tool and “ends” or empowerment in the management of Kinabalu National Park (KNP) in Sabah state of Malaysia and the Kayan Mentarang National Park (KMNP) in North Kalimantan of Indonesia, two important PAs located in the Heart of Borneo. Following Bali Guidelines by UNEP, three important aspects of public participation at the local level were evaluated by deploying qualitative research methods for key-informant interviews (KII), focus group discussions (FGD), and content analysis of policy documents. In KMNP, policies and legal framework primarily supported local peoples’ participation as “means” in park management, which was also revealed from interviews with KII and in FGD. Local communities had access to surrounding natural resources for livelihoods which is considered to be participation as “ends.” There was no policy support for formal participation of local people in KNP management, but recent informal permission to use designated park areas for farming and eco-tourism can be seen participation as “means” and as “ends.” To achieve both of “means” and “ends” fully, participation needs to be integrated into national parks’ legal system.